Komunikacijski protokol društva znanja - Marić, Davor (2019)
Demokratska društva žive po komunikacijskim protokolima. Za sve vrste djelatnosti postoje procedure - formati. Kad Hrvatska ovlada protokolima tj. uskladi poglavlja, ući će u Europsku uniju. I dok kao država polažemo prijamni ispit spremnosti za život u europskom informacijskom društvu, bolonjskim procesom poučavamo studente kako se uključiti u društvo znanja. Poučavamo ih informatičkoj pismenosti nužnoj za informacijsku pismenost - kako i gdje naći traženu informaciju. Učimo ih razlikovati društvo znanja, kao društvo forme, formata i protokola od često u praksi prisutnog birokratskog formalizma. Učimo ih informacijskom kapitalizmu koji traži poštivanje zakona i provodi kazne za kršenje pravila. Učimo ih kako pojedinci i države imaju svoje identifikacijske, prezentacijske, dokazne i pokazne kulturne formate i zakone kao njihove regulatore, a da su world wide web, svekoliki mediji i nosači informacija sredstva pronalaženja informacija i znanja.
Democratic societies live by communication protocols. All types of operations follow certain procedures. Croatia as a state will join the European Union when it adapts to its protocols. This will happen when Croatia changes its legislation. In a sense Croatia needs to pass an entrance examination of readiness for living in the european society that is based on communication and knowledge. At the University students are taught by the Bologne educational process on how to join knowledge society. We coach them about computer literacy which is necessary for communication literacy - how and where to find informations. They are taught about differences between the society of knowledge vs. the society that is based on following formal bureaucratic procedures. The latter being widespread in Croatian society. They study about this new form of capitalism (information capitalism) which enforces laws and punishment for violation of legislation. They learn that individuals and states have their identifying, formal, noticeable and visible culture formats and laws as their regulators. Finally, they are taught that the world wide web and all types of media are just instruments of finding information and knowledge
Bibliografske bilješke na kraju teksta.
Sažetak ; Abstract.
Keywords: Društvo znanja -- Komunikacijski protokoli -- Bolonjski proces -- Informacijski kapitalizam -- Kulturni formati